REPORT OF THE ASSOCIATION INTERNATIONALE POUR LETUDE DES ARGILES (AIPEA) NOMENCLATURE COMMITTEE FOR 1996 - Guggenheim S.; Alietti A.; Bain D.C.; Drits V.A.; Formoso M.L.L.; Galan E.; Hudnall W.; Köster H.M.; Paquet H.; Watanabe T. (My University, 1997)
The most recent report of the AIPEA Nomenclature Committee involved the definition and use of the terms 'clay' and clay mineral'; see Guggenheim & Martin (1995;1996). Additional items acted upon by this committee are reported here.